Placental micro- and nanoplastic contamination: A systematic review of eco-exposome pathways to preterm birth and neonatal outcomes - I Nyoman Hariyasa Sanjaya; Wiku Andonotopo; Muhammad Adrianes Bachnas; Julian Dewantiningrum; Mochammad Besari Adi Pramono; Ryan Saktika Mulyana; Evert Solomon Pangkahila; Muhammad Ilham Aldika Akbar; Cut Meurah Yeni; Dudy Aldiansyah; Nuswil Bernolian; Anak Agung Gede Putra Wiradnyana; Adhi Pribadi; Sri Sulistyowati; Milan Stanojevic; Asim Kurjak (Majalah Obstetri & Ginekologi, 2026)
HIGHLIGHTS First comprehensive synthesis of human and mechanistic evidence linking placental micro- and nanoplastic (MNP) contamination to preterm birth and neonatal outcomes. Quantitative human studies demonstrate higher placental MNP burdens in preterm versus term pregnancies. Molecular pathways identified include oxidative stress, ferroptosis-driven syncytiotrophoblast senescence, trophoblast invasion impairment, inflammatory signaling, endocrine disruption, and epigenetic modifications. Clinical and policy relevance: Findings support the need for standardized biomonitoring, maternal exposure mitigation, and the integration of eco-exposome considerations into perinatal care.   ABSTRACT Objective: To systematically review emerging evidence on micro- and nanoplastic (MNP) contamination of the human placenta, explore molecular pathways underlying placental dysfunction, and evaluate associations with preterm birth and neonatal outcomes. Materials and Methods: Following PRISMA 2020 guidelines, literature searches (in PubMed, Web of Science, and Scopus) and grey sources were conducted through July 2025. Inclusion criteria comprised studies detecting MNPs in the human placenta or fetal compartments, mechanistic experiments using human placental models, or reviews addressing pregnancy outcomes. Methodological quality was assessed using AMSTAR-2, ROBIS, or the Newcastle–Ottawa Scale. Data were synthesized into three evidence domains: human biomonitoring, molecular pathways, and clinical implications. Results: Twenty studies met the inclusion criteria. MNPs were consistently detected in the human placenta, amniotic fluid, cord blood, and meconium, with higher burdens in preterm versus term placentae. Mechanistic studies demonstrated oxidative stress, ferroptosis-mediated syncytiotrophoblast senescence, impaired trophoblast invasion, inflammatory responses (IL-6, TNF-α, NLRP3 activation), endocrine disruption (altered ß-hCG and progesterone signaling), and epigenetic modifications. These pathways converge to impair nutrient and oxygen exchange and immune tolerance, increasing the risks of preterm birth, fetal growth restriction, low birth weight, and neonatal respiratory and metabolic vulnerability. Conclusion: Micro- and nanoplastic contamination of the human placenta is increasingly documented and biologically plausible as a contributor to preterm birth and neonatal morbidity. These findings support urgent investigation of exposure mitigation, standardized biomonitoring, and the integration of eco-exposome risks into perinatal clinical practice and policy.